Study on the mechanical properties of anisotropic red sandstone under point load strength test and uniaxial compression strength - Meiqian Wang; Changxing Zhang; Binghui Song; Haiming Liu; Wei Xu (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
The red sandstone of Xiaopu 3# branch Cave in the Yuxi section of the Central Yunnan Water Diversion Project was taken as the research object. The uniaxial compression strength and point load strength test are conducted from the perspectives of vertical and parallel stratifications, respectively, and then the anisotropy of red sandstone was analyzed in detail. The data obtained from the field and laboratory test was analyzed, and the conversion relationship between point load strength index and uniaxial compression strength is a power function under both parallel stratification and vertical stratification. The study results showed that: The mechanical properties of red sandstone have obvious anisotropy. The difference in its mechanical properties is particularly evident in UCS and point load tests and Is(50) and UCS under vertical stratification are significantly greater than Is(50) under parallel stratification. The point load strength correction index m of red sandstone is m = 0.4096 under parallel stratification, and m = 0.4408 under vertical stratification.